Fenomena Burnout dan Analisis Faktor Determinannya Pada Perawat di Rumah Sakit - Wijayati, Ekawati Wasis; Marianingsih (Jurnal Keperawatan Florence Nightingale, 2024)
The health workers who provide the most intense service and accompany patients 24 hours in the hospital are nurses. Besides that, nurses can also serve and accompany patients with various characteristics ranging from age, occupation, and socio-economic status to the disease they are suffering from. This can cause work burden and stress on nurses which, if it continues continuously, can cause burnout. The term burnout is used to express a state of low physical and mental energy as a result of prolonged stress. The research aimed to determine the prevalence of burnout among nurses at Z Hospital Batu City and its various determinants. This research is analytical survey research with a cross-sectional approach and a sample size of 46 nurses. Sampling technique used purposive sampling. This study showed that most nurses experienced low-category burnout in all work units, namely the prevalence of low-category burnout in ER nurses was 66,7%, Irna nurses 75%, and Irja nurses 85,7%. Based on statistical tests with chi-square and kolmogorov-smirnov on the determinant factors of burnout (gender, age, work unit), the results obtained were that all factors had p > 0.05, which means there was no correlation between the factors of gender, age, and work unit on the incidence of burnout among nurses at Z Hospital, Batu City. Therefore, it is necessary make efforts to manage burnout in nurses so that it does not affect the performance and quality of nursing services